Detection of HBME-1 and Galectin-3 by Immunohistochemistry in Follicular Lesions - Wijdan B. Abid (Journal of Global Pharma Technology, 2018)
The main problem established by a discovery of a thyroid nodule is to discriminate between a benign and malignant lesion. Differential diagnosis between follicular thyroid cancer (FTC) and benign follicular thyroid adenoma (FTA) is a great challenge for even an experienced pathologist and requires special effort. A developing number of some encouraging IHC markers for the differential diagnosis of thyroid lesions have emerged, including, Hector Battifora mesothelial (HBME-1) and galectin-3 (Gal-3). There was significant positive correlation between Galectin-3 and HBME-1 in follicular carcinoma and follicular variant of papillary carcinoma (r= 0.380, P= 0.041) and (r= 0.315, P=0.047) respectively. There was no significant correlation between Galectin-3 and HBME-1 in follicular adenoma and follicular hyperplasia. Immunohistochemical expression of Galectin-3(Gal-3) there was highly significant difference (P<0.001) among study groups (FC, FVPC, FA, follicular hyperplasia) while there was no significant difference in mean of immunohistochemical score of Galectin-3 between follicular carcinoma, follicular variant of and papillary carcinoma (P>0.05); however, carcinoma of both types showed significantly higher Galectin-3 score than both follicular adenoma and follicular hyperplasia (P<0.001). In addition, the score of follicular adenoma was significantly greater than that of follicular hyperplasia (P<0.05). Immunohistochemical expression of HBME-1 immunohistochemical expression of HBME-1was highly significance among study groups (FC, FVPC, FA, follicular hyperplasia) while there was no significant difference in mean score between follicular carcinoma and follicular variant of papillary carcinoma (P>0.05); however, carcinoma of both types showed significantly higher HBME-1 score than both follicular adenoma and follicular hyperplasia (P<0.001). In addition, the score of follicular adenoma was significantly greater than that of follicular hyperplasia (P<0.05).Keywords: Galatin-3, HBME-1, Thyroid.